KONTRIBUSI POWER OTOT LENGAN DAN BAHU DAN KELENTUKAN PERGELANGAN TANGAN DENGAN KETEPATAN SMASH PADA TIM BOLA VOLI BINTANG MUDA KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Megi Hariandri; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : After observation and observation studies conducted by the author in the field, and also based on information from trainers and athletes,That Team volly bintang muda districts toar regency of kuantan singingi until now has not been able to show the maximum achievement. There are still many players who fail at the time of smash, As the ball is often out of the field and sometimes stuck on the net or the ball can be restored by the opponent with the young. In accordance with the background problems and problem formulation, this study aims to find out,power contribusion of muscle arm and shoulder establishing of hands with smash precision on the team volly ball bintang muda districts toar regency of kuantan singingi. The sample population in this study is the volley ball team bintang muda who are still active follow the training of 12 people. Instruments in this study are Two hand medicine ball putt, flexibility of the wrist and smash accuracy test. The data obtained in the analysis by using product moment correlation. Based on the results of research that has been authors described in the previous chapter, it can be concluded that From the results obtained, power muscles of the arms and shoulders have no connection with the accuracy of smash on the volley ball team bintang muda districts toar regency of kuantan singingi. There is no joint relationship between the muscle strength of the arms and shoulders and the flexibility of the wrist with the accuracy of the team smash volley ball team bintang muda districts toar regency of kuantan singingi.Key Words: Power the Muscles of the Arms and Shoulders ,Flexibility of the Wrist and Smash Accuracy